Modes of cannabis administration in the year prior to conception among patients in Northern California. (June 2022) - Young-Wolff, Kelly C.; Adams, Sara R.; Brown, Qiana L.; Weisner, Constance; Ansley, Deborah; Goler, Nancy; Skelton, Kara R.; Satre, Derek D.; Foti, Tara R.; Conway, Amy
Highlights: Smoking and edibles are the most common modes of preconception cannabis use. 46% of individuals with cannabis use during the year before pregnancy used >1 mode. Modes of preconception cannabis use vary with socio-demographics and use frequency. Continued surveillance can help guide targeted prevention and intervention strategies. Abstract: Cannabis use among individuals before and during pregnancy is increasing alongside the proliferation of new products with various modes of administration. Preconception cannabis use is a strong predictor of prenatal cannabis use. Yet little is known about how individuals administer cannabis during the preconception period, particularly in socioeconomically vulnerable populations. This study examined the prevalence and correlates of modes of cannabis administration (smoke, vape, blunts, edible/oral, dabs/wax, lotion/topical) during the year before conception, among patients who self-reported preconception cannabis use during universal screening in prenatal care. Descriptive statistics included sociodemographic characteristics, preconception cannabis use frequency, and modes of administration. Chi-square tests examined whether mode was associated with sociodemographic characteristics and use frequency. The sample (N = 11, 936, screened from February 2020-May 2021) was 59.8% non-White and 26.1% were < 26 years old; 50.7% reported monthly or less, 21.8% weekly, and 27.4% daily preconception cannabis use; 69.7% smoked (any method), 34.5% smoked blunts, 53.4% used edibles/oral, 28.2% vaped, 9.9% used lotion/topical; 54.2% reported 1 mode, 30.4% reported 2 modes, 15.4% reported 3+ modes. Smoking was more common among daily users, younger patients, those with greater neighborhood deprivation, and Black and Hispanic patients, while edibles/oral were more common among ≤ monthly users, older patients, those with less neighborhood deprivation, and Asian patients. Use of other modes also varied by sociodemographic characteristics and use frequency. Research is needed to understand preconception cannabis use in vulnerable subpopulations, continuation of use during pregnancy, and whether health risks associated with preconception and prenatal cannabis use differ by administration mode.